Impact of protein, lipid and carbohydrate on the headspace delivery of volatile compounds from hydrating powders - Fisk, Ian; Boyer, Maxime; Linforth, Rob S.T. (Springer, 2012)
The release of volatile compounds, such as aroma, from a food material during hydration is of wide relevance to the food industry. To this end, dry powders of varying chemical composition were hydrated in a controlled system to investigate the impact of varying composition (protein, lipid and carbohydrate) on the delivery rate of volatile compounds to the headspace. Additional lipid and carbohydrate reduced the concentration of volatile compounds in the headspace and accelerated their rate of delivery to the headspace. Protein had no measurable impact. Of the volatile compounds measured, 2,3 butanedione and acetaldehyde were shown to be released slowly into the headspace, and pyrrol, methyl acetate and pyridine were released rapidly; this differential release rate was strongly correlated with hydrophobicity and would indicate that during hydration there is a temporal dimension to the relative abundance of volatile compounds in the headspace.